A healable polyethylene adhesive using poly(ethylene methacrylic acid) (EMAA) for three-layer pipe coatings. Issue 1 (14th January 2021) - Dell'Olio, Carmelo; Zhang, Jane; Leong, K H; Samsudin, M Shamsul F; Varley, Russell J
Abstract: Poly(ethylene methacrylic acid) (EMAA) has been used here as a thermally activated healing agent (HA) in three layered polyolefinic (3LPO) pipe coatings for the first time. The EMAA (HA) is blended with a linear low density polyethylene (LLDPE) modified with maleic anhydride (MAH) to create a healable multi-functional adhesive (HAMA), which is used to bind the fusion bonded epoxy primer and high density polyethylene topcoat layers together. Different compositions of the HA and modified adhesive were trialled for their healing efficiency using three different healing conditions to explore the effect of increasing temperature and applied load or force. The standard healing protocol used a healing temperature of 110 °C and an applied load of 120 N for 60 min. A high temperature variant increased the temperature to 120 °C while a high load variant increased the applied force to 240 N. Using a 1:1 HAMA adhesive, healing efficiencies of about 70% were achieved for the standard healing condition. Increasing the applied load to 240 N decreased healing to between 64% and 68% depending on the healing measurement, but at 120 °C healing increased to between 82% and 84%. Regardless of the healing condition, overall healing efficiency increased with increasing EMAA (HA) concentration. This study also provided insight into the healing mechanism of the HAMA adhesives by highlighting some necessary features for healing. A bi-phasic microstructure consisting of large EMAA nodules with sufficient adhesion to the MAH-modified LLDPE was identified as being critical. Furthermore, increasing healing temperature increased healing efficiency due to the enhanced flow of EMAA and increased mobility of the polyethylene. Although these results are preliminary in nature, they do provide significant promise that multifunctional HAMA adhesives can be applied as simple, effective and repeatable 3LPO self-healing pipe coatings.